How does performance of long and short case examination correlated with objective structured clinical examination (osce) performance in final undergraduate professional examination - Husbani, M.A.R.; Myat Moe Thwe, Aung; Harmy, Mohamed Yusoff; Norwati, Daud (2017)
Background: There are many methods in assessing clinical competence. OSCE, clinical long case and clinical short case are among the widely used method in medical programmes in Malaysia Objective: To determine the correlation of clinical bedside performance with the overall OSCE performance, communication skills OSCE and psychomotor skills OSCE. Methods: Fifty-seven undergraduate medical students sat for the Professional II (final) examination for the session of 2016/2017 in Faculty of Medicine, University Sultan Zainal Abidin, Terengganu, Malaysia. The clinical components exam was 12 interactive OSCE stations, one long case and three short cases. OSCE comprised of seven communication skills stations and five psychomotor skills stations. Their results were analysed using SPSS Version 22. Pearson’s correlation test was applied to determine the correlation between bedside performance and the three variables. Results: The correlation coefficient (r) values for OSCE performance, communication skills performance and psychomotor skills performance are 0.488 (p<0.001), 0.369 (p=0.005) and 0.458 (p<0.001) respectively. Conclusion: There was statistically significant, fair to good positive correlation between overall, communication skills, and psychomotor skills OSCE and clinical bedside marks. Psychomotor skills performance showed better correlation than communication skills. Steps may need to be taken to improve the correlation especially in communication skills stations.